Feasibility of offering nicotine replacement therapy as a relapse prevention treatment in routine smoking cessation services - Turner, Jessica; McNeill, Ann; Coleman, Tim; Bee, Jo Leonardi; Agboola, Shade (BIOMED, 2013)
Background: National Health Service stop smoking services (NHS SSS) in the UK offer cost- effective smoking cessation services. Despite high abstinence rates after acute cessation treatment, the majority of clients have relapsed by one year. Several interventions have been identified, from trial data, as effective in preventing relapse to smoking. This study investigated uptake, feasibility and acceptability of offering nicotine replacement therapy (NRT) as a relapse prevention intervention (RPI) in NHS SSS. Methods: Eligible smokers who had successfully completed acute cessation treatment using NRT at Nottingham City NHS SSS between April 2010 and January 2011 were offered the RPI and the rate of uptake was monitored. Consenting individuals completed a baseline questionnaire, providing demographic and smoking behaviour data. The RPI consisted of using NRT for a further 12 weeks after initial cessation-orientated treatment had ended. At a six-month review, self-reported smoking status was assessed via telephone. Anonymised demographic data on NHS SSS users who did not agree to participate in the study were retrieved from NHS SSS records and used to determine the presence of any socio-demographic differences between individuals who agreed to participate in the study and those who did not. Semi-structured telephone interviews were conducted with a selection of participants; these were audio-recorded, transcribed and analysed to identify participants’ views on the RPI. Results: Of 493 stop smoking service clients who were assessed, 260 were eligible for and offered the RPI and 115 (44%, CI 38%- 50%) accepted. Individuals who accepted NRT were significantly more likely to be older (p < 0.001) and to pay for their prescriptions (p < 0.001). Quitters who had never worked or were unemployed were significantly less likely to accept the offer of relapse prevention compared to those in routine and manual occupations (55% reduction in odds, p = 0.026). Interview findings revealed that clients who accepted extended NRT felt the longer duration of pharmacological and psychological support were both valuable in helping them to remain abstinent. Conclusion: In routine smoking cessation service care, it is feasible to offer clients extended courses of NRT as a RPI. The RPI was acceptable to them as almost half of the eligible clients offered this treatment accepted it. Keywords: Smoking relapse prevention, Nicotine replacement therapy, Feasibility study, Smoking cessation service